Comparison of the Effectiveness of the Weighted Moving Average Method and Single Exponential Smoothing for Forecasting the Number of Telkomsel Customers - Idzanul Iksan Sinatra; Bambang Pramono; Statiswaty Statiswaty (Informatics Engineering Department of Halu Oleo University, 2019)
PT. Telkomsel almost controls 90% market share in Indonesia with more than 196 million subscribers in 2017. Grapari Kendari City as a service center for Telkomsel customers in Southeast Sulawesi still does not have a system to predict the number of its customers. This resulted in the loss of potential services that should have been able to be provided such as the construction of branch offices in areas that have the potential to have a high number of customers to provide overall service to customers. To overcome this problem, a system will be created that can assist in managing customer data and predict the number of customers using forecasting algorithms with weighted moving average methods and single exponential smoothing methods as a comparison to see the effectiveness of the methods used. After a comparative analysis was found, 6 of the 8 cities / regencies used as the research data showed the Mean Absolute Error (MAD), the Mean Squared Error (MSE) and the Mean Absolute Percentage Error (MAPE) Single Exponential Smoothing method smaller than the Weighted Moving Average method. This is because the Single Exponential Smoothing method is in accordance with the data pattern of growth in the number of Telkomsel Region Southeast Sulawesi customers, namely horizontal data patterns or data patterns that fluctuate around a constant average value.